Perkembangan dan Konsep Dasar Manajemen Humas dalam Dunia Pendidikan: Tinjauan Historis - Hadi, Abdul (LP3M Universitas Islam Zainul Hasan Genggong, 2018)
This journal discusses the history of development, definition, function, objective and scope of public relations management globally then we are required to understand and glance back the history of the emergence of